Empowered and Supported: Unpacking the Predictive Role of Self-Efficacy and Social Support in Shaping Teacher Resilience in Inclusive Elementary Schools - Ratna Yanita Kusuma; Kartika Nur Fathiyah (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The implementation of inclusive education remains hindered by insufficient supporting facilities, presenting considerable challenges for teachers. Failure to effectively manage these challenges increases psychological vulnerability and threatens teacher resilience. This study investigates self-efficacy and social support as joint predictors of teacher resilience in inclusive elementary schools, offering a novel contribution by examining their combined influence across specific resilience dimensions. Using a quantitative approach and an ex post facto design, data were collected from 156 inclusive elementary school teachers in Bantul Regency. The study employed structural equation modeling with the partial least squares (SEM-PLS) method. Results showed that both self-efficacy and social support significantly predicted overall teacher resilience (R² = 0.357, Q² = 0.301), as well as each dimension: personal competence and persistence (R² = 0.352), family cohesion (R² = 0.169), social skills and peer relationships (R² = 0.264), and spiritual influences (R² = 0.190). The study highlights that resilient teachers are supported by both internal confidence and external networks, enabling them to sustain professional performance in inclusive settings. This research advances the field by providing empirical evidence for a multidimensional predictive model of resilience, which had not been sufficiently addressed in prior studies. These findings suggest the need for interventions that integrate psychological empowerment and social support mechanisms to strengthen teacher resilience in inclusive education.